PENGUATAN UMKM MELALUI IMPLEMENTASI PRODUK LOKAL SABUN DAUN SIRI DAN KERIPIK DAUN SAWI DESA KALEB PANTAR TIMUR KAB. ALOR-NTT - Imanuel Puling (Adiba Aisha Amira, 2025)
Strengthening Micro, Small, and Medium Enterprises (MSMEs) is a crucial strategy for improving community welfare, particularly in rural areas with abundant natural resource potential. This research focuses on the implementation of local products, namely betel leaf soap and mustard green chips, in Kaleb Village, Pantar Timur District, Alor Regency, East Nusa Tenggara (NTT). The use of betel leaves as a raw material for natural soap offers health and hygiene benefits, while the innovation of mustard green chips creates a healthy, nutritious, and marketable food product. The methods used included community empowerment, processing training, and the use of technology and digital marketing to expand the market. The results of the activities indicate that the community is able to develop production skills, increase the added value of local products, and expand business opportunities. Thus, the implementation of these local wisdom-based products not only strengthens the community's economy but also encourages village independence and strengthens local cultural identity.